Pengembangan Sistem Informasi Persediaan Barang, Harga Pokok Produksi, Dan Transaksi Penjualan Berbasis Web (Studi Pada Son Screen Printing Sidoarjo) - Adytria Fadli Pamungkas; Niken Hendrakusma Wardani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Son Screen Printing Sidoarjo is a company who produces garment based on customer demands. The company already had large profit but less inventory and transaction record. This causes the company doesn't has sources for reporting SPT Tahunan, company can't provide inventory and transactions recapitulation for forcasting future inventory and customer demand in a certain period, also information that owner has not shared real time with employee. They determined the cost of production by manual counting so sometimes has a miscalculate and take more time to serve customer. Based on the research problem, solutions given are, to develop inventory information system, cost of goods production, and web-based sales transaction for Son Screen Printing Sidoarjo. Providing information system based on Waterfall software development model. The test runs white-box testing, black-box testing, compatibility testing, user acceptance testing, and system time performance evaluation. From the results of software testing conducted can be concluded that the information system is feasible to use